Intellectuals, inequalities and transitions prospects for a critical sociology - Demeter, Tamás 1975- (Studies in critical social sciences, 2020)
This volume is devoted to the central themes in Iván Szelényi?s sociological oeuvre comprising of empirical explorations and their theoretical refinement in the last 50 years. The contributors have been asked to take interpretive and critical stances on his work, and to clarify the relevance of his insights. Iván Szelényi has been asked to write a concluding chapter, and respond to the present reflections on his work. The ensuing volume discusses Szelényi?s captivating scholarship as being grounded in a complex program for the political economy of socialisms and post-socialist capitalisms, and introduces him as a neoclassical sociologist whose research projects continue to investigate inequalities created by the interaction of markets and redistributive structures in various societies.00Contributors include: Dorothee Bohle, Tamás Demeter, Gil Eyal, Béla Greskovits, Michael D. Kennedy, Tamás Kolosi, Karmo Kroos, Victor Nee, David Ost, Iván Szelényi, Bruce Western